A Comparison Study on the Rhetorical Structures of Abstracts in Two Disciplines Indexed Journals - Nurhayati S.; Fadilah (ITScience (Information Technology and Science), 2024)
Abstracts offer a concise summary of a study, helping readers determine whether to read the full article, as they serve as the initial point of access to knowledge and are among the first freely available